7: INTEGRATED PATHWAY ANALYSIS OF MICRORNA EXPRESSION IN PLASMA OF OVARIAN CANCER (OVCA) PATIENTS SHOWS LACK OF BH3 PROTEIN DEPENDENT SIGNALING. Issue 3 (23rd February 2016) - Shapira, I; Naboush, A; Banavali, A; Neculiseanu, E; Guddati, K; Kopf, M; Mason, C; Lee, A
Abstract : Purpose of Study: More than 100, 000 pelvic surgeries to remove ovarian masses (BOM) are performed yearly in the USA only 8% of those remove ovarian cancer. Circulating microRNA are biomarkers for disease detection. Purpose of study: 1. To analyze patterns of microRNAs in women with BOM vs. OvCa 2. Discover pathway involved malignant transformation. Methods Used: Plasma from 32 women OvCa, 24 controls 32 (BOM) was analyzed using ABI Taqman OpenArray MicroRNA pools A and B to measure the expression of 754 known miRNAs .Real-time PCR was performed on the Taqman Open Array MicroRNA arrays using the Applied Biosystem Open Array Real-Time PCR system. Data were processed using the OpenArray Real-Time qPCR Analysis software and exported for analysis using the Applied Biosystems DataAssist Software Data analysis was done with the R programming language. A cutoff for Ct values at 30 was used. MiRNAs with Ct values higher than 30 were considered not detected. Data was normalized using a mean-centering restricted (MCR), a modification of the traditional delta Ct method and uses miRNAs which are expressed in all samples for data normalization. Statistical analysis was performed via custom scripts based on the R/Bioconductor package LIMMA (Linear Models for Microarray). Summary of Results: BOM had higher expression (2–14 fold higher) of miRs −195, −126, −139-5p, −27b, −127, −152, −28, −106b, −17, −363, −181a, −192 relative to OvCa (p<0.0006). OvCa over-expressed of miRs −1274a, −720 and −625-3p (p<0.0007). Reactome pathway analysis detected involvement of miRs into pathways of activation of BAD, PI3/AKT signaling in CD28 and activation of BH3 in BOM these pathways were not detected in OvCa (p<0.000596). Conclusions: BOM patients have immune recognition and pro-apoptotic protective circulating microRNAs. It is unknown whether miRs originate in ovary or another tissue. Recent work shows that BH3 mimetics are very effective in inducing cancer cell death.